FINANCIAL REHABILITATION OF ENTERPRISES: STRATEGIES AND CHALLENGES - Urunova Maftuna Gayratovna (Bright Mind Publishing, 2025)
The article discusses the key approaches and mechanisms of financial rehabilitation for enterprises facing economic distress. It analyzes internal and external factors contributing to financial instability and presents effective restructuring strategies. The study highlights the importance of diagnostics, crisis management, and the role of stakeholders in recovery processes. Special attention is given to the legal and institutional frameworks that support enterprise rehabilitation in transitional economies.
Keywords: Financial rehabilitation, enterprise restructuring, crisis management, insolvency, financial diagnostics, transitional economy.